2016
DOI: 10.5114/ceji.2016.58311
|View full text |Cite
|
Sign up to set email alerts
|

A natural herbal remedy modulates angiogenic activity of bronchoalveolar lavage cells from sarcoidosis patients

Abstract: Sarcoidosis is a systemic inflammatory disease with abnormally high angiogenic activity of inflammatory cells. Reumaherb preparation consisting of three herbs: Echinacea purpurea, Harpagophytum procumbens, and Filipendula ulmaria, and it exerts anti-inflammatory, antioxidant, and analgesic activity and stimulates regenerative and immunological processes.The aim of this paper was to estimate the effect of Reumaherb on immunological angiogenesis induced by bronchoalveolar lavage (BAL) cells collected from six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study found that oral administration of 1.2 mg Reumaherb to mice exhibited potential anti-inflammatory, as well as anti-angiogenic, effects on mononuclear cells. It was, however, concluded the Reumaherb concoctions showed excellent concentrations of angiogenesis which might be used for rheumatoid arthritis patients [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study found that oral administration of 1.2 mg Reumaherb to mice exhibited potential anti-inflammatory, as well as anti-angiogenic, effects on mononuclear cells. It was, however, concluded the Reumaherb concoctions showed excellent concentrations of angiogenesis which might be used for rheumatoid arthritis patients [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…As our study indicates, Reumaherb can display anti-angiogenic properties when applied orally at a dose of 1.2 mg per mice. In this research immunological angiogenesis induced by bronchoalveolar cells (BAL) isolated from patients with sarcoidosis and grafted into Balb/C mice skin was diminished [ 41 ] by this preparation. Similar experiments with Reumaherb was performed on mononuclear cells derived from RA patients.…”
Section: Natural Antioxidants Inhibited Angiogenesismentioning
confidence: 99%